Review of Palaeobotany and Palynology - Review of Palaeobotany and Palynology (Elsevier, 2026)
The Review of Palaeobotany and Palynology is an international journal for articles in all fields of palaeobotany and aquatic and terrestrial palynology dealing with fossil remains of biota composed of persistent organic remains derived from marine, freshwater and terrestrial environments. Original contributions and comprehensive review papers should appeal to an international audience. Typical topics include systematics, evolution, palaeobiology, palaeoecology, biostratigraphy, biogeochemistry, biochronology, palaeoclimatology, paleogeography, taphonomy, palaeoenvironmental reconstructions, and practical applications of palaeobotany and palynology, e.g. in coal and petroleum geology, forensics, and archaeology. The journal especially encourages the publication of articles in which palaeobotany and/or palynology are applied for solving fundamental outstanding geological and biological problems, notably with innovative and interdisciplinary approaches.
FI 0.74
Q2
Keywords: Life Sciences; Plant Science; Ciencia de las plantas; Acuerdos transformativos; Transformative agreements; Paleobotánica; Palinología acuática y terrestre; Entornos marinos, de agua dulce y terrestres